Four common glomulin mutations cause two thirds of glomuvenous malformations ("familial glomangiomas"): evidence for a founder effect. Issue 2 (2nd February 2005) - Brouillard, P; Ghassibé, M; Penington, A; Boon, L M; Dompmartin, A; Temple, I K; Cordisco, M; Adams, D; Piette, F; Harper, J I; Syed, S; Boralevi, F; et al.
Abstract : Background: Glomuvenous malformation (GVM) ("familial glomangioma") is a localised cutaneous vascular lesion histologically characterised by abnormal smooth muscle-like "glomus cells" in the walls of distended endothelium lined channels. Inheritable GVM has been linked to chromosome 1p21-22 and is caused by truncating mutations in glomulin . A double hit mutation was identified in one lesion. This finding suggests that GVM results from complete localised loss of function and explains the paradominant mode of inheritance. Objective: To report on the identification of a mutation in glomulin in 23 additional families with GVM. Results: Three mutations are new; the others have been described previously. Among the 17 different inherited mutations in glomulin known up to now in 43 families, the 157delAAGAA mutation is the most common and was present in 21 families (48.8%). Mutation 108C → A was found in five families (11.8%), and the mutations 554delA+556delCCT and 1179delCAA were present together in two families (4.7% each). Polymorphic markers suggested a founder effect for all four mutations. Conclusions: Screening for these mutations should lead to a genetic diagnosis in about 70% of patients with inherited GVM. So far, a mutation in glomulin has been found in all GVM families tested, thus demonstrating locus homogeneity.